1992
DOI: 10.1002/bjs.1800790322
|View full text |Cite
|
Sign up to set email alerts
|

Serum electrolytes and capillary blood gases in the management of hypertrophic pyloric stenosis

Abstract: The purpose of this study was to assess whether the concentration of serum chloride and other variables, namely serum sodium, potassium and bicarbonate, can be used to predict metabolic acid-base status in infants with hypertrophic pyloric stenosis (HPS) and to assess whether such a prediction is influenced by the state of hydration. One hundred and sixty-three infants with HPS who had at least one set of serum electrolyte and capillary blood gas estimations performed after admission were studied retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…These results correspond to those of a previous study [16]. Others described a slow decline in Na + concentration as the symptoms persisted [13] and a negative correlation between the Na + and 3 HCO − levels [15]. In a recent Chinese study, hyponatremia was found in 54% of infants with IHPS [8].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results correspond to those of a previous study [16]. Others described a slow decline in Na + concentration as the symptoms persisted [13] and a negative correlation between the Na + and 3 HCO − levels [15]. In a recent Chinese study, hyponatremia was found in 54% of infants with IHPS [8].…”
Section: Discussionsupporting
confidence: 90%
“…However, these mechanisms appear to be less important in infants [24]. In concordance with the results of a previous study [15], a correlation analysis confirmed a strong negative correlation between st 3 HCO − and K + (p = 0.001, Table 4). In our cohort, we predominantly found a highly normal serum K + concentration, and less than 10% of the infants had values below 3.5 mmol/l.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…12 Additionally, 12-hourly blood sampling was thought to be the most appropriate by the parents within the consensus committee. Previous authors have described reductions in duration of hospitalization by using standardized post-pyloromyotomy feeding regimens.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,8,13 Adequate resuscitation is reported as plasma chloride concentration >106 mmol/L in some studies, while others suggest chloride >100 mmol/L or even >97 mmol/L as sufficient prior to surgery. 4,[13][14][15][16] These variabilities in cutoff values also exist for other laboratory variables. To correct metabolic alkalosis and electrolyte disturbances, fluid resuscitation is needed.…”
Section: Introductionmentioning
confidence: 95%